SP0025 Neutrophil microparticles - what do they do?. (23rd January 2014) - Perretti, M.
Abstract : Microparticles (MPs) are small vesicles shed from the plasma membrane that retain unique markers and mediators of their parent cell, enabling them to exert independent functions. Elevated levels of circulating MPs are associated with a number of cardiovascular and inflammatory pathologies, yet the extent of their contribution remains uncertain. An intriguing notion is that MPs originating from different cell types or after different stimulation can exert deleterious or protective effects. Proteomic analysis of neutrophil-derived MP - generated from cells stimulated in two different settings - revealed >400 hits of which only ∼50% were identical. Coupling proteomic to western blotting and flow cytometry analyses allowed us to identify Alpha-2-Macroglobulin (A2M) as a novel determinant of the CD66b+ MP fraction in plasma samples of patients suffering from Giant Cell Arteritis, Rheumatoid Arthritis and sepsis, with over double the levels measured in healthy control or osteoarthritis plasma (n=10-15; P<0.01). An interesting dichotomy emerged from septic patients who survived the event and those who did not survive. A series of experimental investigations demonstrated that A2M/CD66b+ neutrophil-derived MP activated endothelial cells under flow, preserved neutrophil chemotactic receptors and, ultimately, afforded protection in a model of sepsis. In summary, the take-home-message of this work are that: i) neutrophil-derived MP are heterogenous in their nature, and could be generated in a stimulus-dependent fashion, to elicit a variety of biological functions; ii) plasma Alpha-2-Macroglobulin/CD66b+ MPs could become a novel biomarker for systemic inflammation in human pathologies and could be quantified to monitor progress and clinical management. Funding: British Heart Foundation, Arthritis Research UK and The Wellcome Trust. Disclosure of Interest: None Declared